2003
DOI: 10.1074/jbc.m212853200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of the Cell Cycle Regulator CDH1 and Its Regulation by Phosphorylation

Abstract: The anaphase-promoting complex activated by CDC20 and CDH1 is a major ubiquitination system that controls the destruction of cell cycle regulators. Exactly how ubiquitination is regulated in time and space is incompletely understood. Here we report on the cell cycle-dependent localization of CDH1 and its regulation by phosphorylation. CDH1 localizes dynamically to the nucleus during interphase and to the centrosome during metaphase and anaphase. The nuclear accumulation of CDH1 correlates with a reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 79 publications
9
68
0
Order By: Relevance
“…were nuclear, which corresponded to the reported active form of the yeast and human orthologues (23,24).…”
Section: Ccs52a1 and Ccs52a2 Are Expressed At The Proximal And Distalmentioning
confidence: 67%
“…were nuclear, which corresponded to the reported active form of the yeast and human orthologues (23,24).…”
Section: Ccs52a1 and Ccs52a2 Are Expressed At The Proximal And Distalmentioning
confidence: 67%
“…However, there are also reports that Cdh1 levels oscillate during the cell cycle at least in human cells Hsu et al, 2002). The subcellular localization of Cdh1 is cell cycle regulated (Jaquenoud et al, 2002;Zhou et al, 2003) and Cdh1 is nuclear during G1 and in the cytoplasm between S phase and the end of mitosis (Jaquenoud et al, 2002). Cdkdependent phosphorylation leads to efficient inactivation of Cdh1 by nuclear export (Jaquenoud et al, 2002) and prevention of APC binding Jaspersen et al, 1999;Lukas et al, 1999;Kramer et al, 2000), thus restricting APC Cdh1 activity to the points in the cell cycle when Cdk activity is low.…”
Section: Regulation Of Apc Activitymentioning
confidence: 99%
“…Previous work suggested that the cellular presence of Cdh1 is in the nucleus. 21,22 Localization of Skp2 has been variable depending on cell type. [23][24][25][26][27] To assess the localization of Cdh1 and Skp2 in Mv1Lu cell, we performed immunocytochemistry in the presence and absence of TGFβ.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%